Positives outweighing negatives: the experiences of Indian crowdsourced workers. (1st April 2016) - ,; ,
Abstract : This article reports on an empirical study of Indian freelancers working via Elance-oDesk (now renamed Upwork). In a qualitative approach, data were gathered from 24 freelancers across India through in-depth telephone interviews and analysed thematically. The core finding that 'the positives outweigh the negatives' highlighted the fact that the challenges were eclipsed by what these freelancers gained, in terms of employment opportunities, income, skill utilisation and enhancement, career progression, emphasis on merit, international exposure, flexibility and platform-based protection of worker interests. Participants' favourable experiences are explained by the nature of the Indian labour market. The study extends insights into crowdsourcing for paid work which has so far been largely researched in the West and has focused disproportionally on the Amazon Mechanical Turk platform.